Pre-Service Mathematics and Primary School Teachers’ Design and Application of Mathematics Materials in Woodworking Workshops - Yılmaz, Demet Deniz; Kartal, Ayça (My University, 2024)
This study addressed in-class activities with concrete mathematics (math) materials developed by preservice math and primary school teachers in woodworking workshops and investigated what preservice teachers and primary and secondary school students thought about lectures with those materials. The study employed an embedded mixed design, a predominantly quantitative approach. The sample consisted of 23 preservice math and primary school teachers and 30 secondary school and primary school students in Turkey. Quantitative data were collected using the Torrance Test of Creative Thinking Test. Qualitative data were collected using a Material Design Evaluation Rubric and a Semi-Structured Interview Form. The results showed that the woodworking workshops improved the figural creativity of the preservice math teachers and both the figural and verbal creativity of the preservice primary school teachers. The preservice teachers had no idea about what woodworking workshops were and had difficulty mostly with sandpapering and cutting. The primary and secondary school students stated that they enjoyed using the math materials and learned better. In line with the results of the research, it can be suggested that woodworking workshops be expanded not only in universities but also in primary and secondary schools.